The Philosophy Went Wrong; Good Artists Copy, Great Artists Steal: An insight on Patent Issue in the Smartphone Industry - Shaw, Shashi Kr (Asia Social Issues, 2020)
Smartphone Industry experiencing a high increasing return in the short run indicating the fact that in the long run Increasing return to scale holds, but does the strategy of Patent to restrict entry or to cut competition hold?, Or in other words does the strategy of dominant players to cut the benefit of increasing return to new players and maintain its supernormal profits hold? , rather than going into the painstaking way of each and every case of patent issue, our purpose is to develop the story around the real issue and confirm that the patent as a binding and restrictive mechanism will not hold given the case of a prior art.